Implementation Of Fuzzy Logic On Turbine Ventilators As Renewable Energy - Fahmi Ivannuri; Anggara Trisna Nugraha (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2022)
Energy needs in Indonesia in particular and in the world in general continue to increase. One of the sources of electricity supply, PLTA together with steam power plants (PLTU) and gas power plants (PLTG) indeed play an important role in the availability of electricity. Indonesia, which is an archipelagic country and one of the countries located on the equator, is a factor that Indonesia has abundant wind energy potential. The electrical energy needs of remote communities can be met. Turbine ventilator is a device that functions to circulate air which is placed on the roof of the building that functions as ventilation in residential and industrial buildings. Based on previous research, there are those who examine the use of turbine ventilators as power plants, but there are still many shortcomings that need to be fixed. turbine ventilator that is used to catch the wind and drive the generator, by connecting the wind turbine using a v-belt so that the rotation produced by the generator is maximized. Then the generator produces electrical energy.